Muscle action and cycling position - Tiernan, C.; White, N.; Collins, K.
The goal of this study was to determine the kinematic differences between two cycling positions for the hip and knee joints. We were concerned with determining the changing roles of muscle groups as they relate to cycling position. Our results indicated that there were no major kinematic differences between the standard and aero positions at the knee joint. We based this conclusion on a comparison of linear and angular knee joint velocities which were found to be very similar in both cycling positions. Furthermore, the peak flexion and extension angles for the knee joint were comparable in both positions. However, kinematic differences between the standard and aero cycling positions were found with regard to the hip joint. The hip extensors were maintained in a more optimal position for generating peak extension strength with the cyclist in the aero position. This is due to the maximization of hip extension strength as hip angle approaches 90 degrees (Hamill and Knutzen, 1995). This conclusion is a result of our finding that the hip is more flexed throughout the aero cycling movement when compared to the standard position. In addition, the increased flexion of the hip joint in the aero position could lead to an increased forward-bending-moment of the spine causing increased activity in the erector spinae (Nordin and Frankel, 1989). Our research is consistent with the findings of past studies. Brown et al. (1996) demonstrated that the type and degree of muscle activation is dependent on body position during cycling. In addition, pedaling conditions have been found to significantly affect muscle activity (Jorge and Hull, 1986). This research reinforces our results which indicated that hip extensors were maintained at a more optimal length during the aero cycling position when compared to the standard position. Previous studies have also demonstrated that aspects of gravitational forces are important contributors to locomotor tasks such as pedaling (Brown, et. al., 1996). Observed differences in the locations of the center of gravity of the rider in the two positions and the resulting kinematic differences found in our study supports this conclusion. The results of this study were hampered by lack of statistical analysis, availability of equipment, and time limitations which allowed for the use of only a single subject. The conclusions of this study have simply reinforced previous findings regarding the kinematical differences of cycling positions. Further research into how these kinematic differences contribute to injury and performance in cycling would be very beneficial for both professional and recreational cyclists.